Development and Evaluation of the Wound Healing Effect of a Novel Topical Cream Formula Based on Ginkgo biloba Extract on Wounds in Diabetic Rats. (13th October 2021) - Bardaa, Sana; Makni, Khouloud; Boudaouara, Ons; Bardaa, Tarek; Ktari, Naourez; Hachicha, Selim; Ben Salah, Riadh; Kallel, Rim; Sahnoun, Zouheir; Boufi, Sami
Abstract : Despite advances in diabetes care, impaired diabetic wound healing remains a significant clinical problem. The present study was aimed at developing a novel cream based on Ginkgo biloba extract and investigating its wound healing effect on full-thickness wounds in diabetic rats. The topical formulated oil-in-water emulsion-based cream contains Ginkgo biloba aqueous extract in an amount of about 1% to 5% as an active agent. The prepared formula was subjected to physicochemical assessment and pharmacotechnical characterization. Eighteen alloxan-induced diabetic rats completing full-thickness excisional skin wounds were randomly divided into three groups topically treated with either a normal saline (control group), the reference drug ("Cytol Centella cream®"), and cream based on the Ginkgo biloba extract. The response to treatment was assessed by macroscopic, qualitative, and quantitative histopathological analysis. The prepared formula showed good physicochemical properties. The rheological behavior of the prepared cream followed a non-Newtonian pseudoplastic pattern at different storage temperatures. The cream, which is a macroemulsion with uniform size distribution, remained stable for 6 months. Skin tolerance studies confirmed the compatibility of the cream with the skin. During the experimental trial, the cream based on the Ginkgo biloba -treated group showed significant improvements over the control and reference groups for both general wound appearance and healing dynamics. This increased rate of closure of wounds in diabetic rats was associated with increased collagen synthesis. Our findings showed that the cream could be a promising and innovative topical treatment with Ginkgo biloba extract for the management of acute diabetic wounds.